If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c + 2(c + -3x) + -7 + 6(x + c) = 97 5c + (c * 2 + -3x * 2) + -7 + 6(x + c) = 97 5c + (2c + -6x) + -7 + 6(x + c) = 97 Reorder the terms: 5c + 2c + -6x + -7 + 6(c + x) = 97 5c + 2c + -6x + -7 + (c * 6 + x * 6) = 97 5c + 2c + -6x + -7 + (6c + 6x) = 97 Reorder the terms: -7 + 5c + 2c + 6c + -6x + 6x = 97 Combine like terms: 5c + 2c = 7c -7 + 7c + 6c + -6x + 6x = 97 Combine like terms: 7c + 6c = 13c -7 + 13c + -6x + 6x = 97 Combine like terms: -6x + 6x = 0 -7 + 13c + 0 = 97 -7 + 13c = 97 Solving -7 + 13c = 97 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 13c = 97 + 7 Combine like terms: -7 + 7 = 0 0 + 13c = 97 + 7 13c = 97 + 7 Combine like terms: 97 + 7 = 104 13c = 104 Divide each side by '13'. c = 8 Simplifying c = 8
| 14y=55 | | 6xn/6 | | 53+X=76 | | (8x)+3=(2x)-1 | | 3(x+1)+5(2x-2)=3(3x-4) | | 64-4(-7)(-9)= | | 6w+6(w-2)=36 | | 3x+20=3x-20+x+20 | | r^3+4*r^2+14*r+20=0 | | y+39=4y | | 4m-7m=15 | | (2x)-12=(4+x)8 | | 1/2xplus13=9 | | 3*(5x-2)+4x=9x+6-2x | | 2(8y-8)-(2y+7)= | | y=X^2-69X-108 | | s=9+11 | | 11-4x=3-2x | | -2n+6=-2n+6 | | x(2)-16x=-63 | | 3.8+32-4.68-4= | | c^2+14c-13=0 | | 7=l-5 | | 10y=14 | | 8/9=x/18 | | 3(20-1y)+14y=203 | | X+93=17 | | (x+109)(x+89)=180 | | 12x+2-3x=10+-2x | | j+9=13 | | g(x)=-4f(x) | | 3*2-13y=6 |